CORRELATION BETWEEN CONSCIENTIOUSNESS AND READING COMPREHENSION ACHIEVEMENT - Intan Permata Sari; Ida Rosmalina; Erlina Erlina (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2019)
Conscientiousness is one of the personality traits that defined as an individual tendency to be organized, thorough, controlled, decisive and dependable. This study was done to find out (1) the correlation between conscientiousness and reading comprehension achievement, (2) the significant difference in conscientiousness and reading comprehension achievement between male and female students, (3) the significant difference in conscientiousness and reading comprehension achievement between social science students and natural science students, and (4) the contribution of conscientiousness to reading comprehension achievement. The population of the study was the eleventh grade students of SMA Negeri 20 Palembang. One hundred students were purposively taken as sample on the basis of equal numbers of gender and major. To collect the data, reading comprehension achievement test and conscientiousness questionnaire were distributed to students and analyzed statistically. The findings showed conscientiousness and reading comprehension achievement significantly correlated (p value = 0.460) and the contribution of conscientiousness to reading comprehension achievement was 20.4%. The significant difference in reading comprehension achievement in gender and major was found; female and natural science students were better. The different result was obtained in conscientiousness. It implied that students tend to had similar perception toward conscientiousness regardless their gender and major.